2023
DOI: 10.2147/prbm.s389806
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Smartphone Use and Social Media Fatigue: The Mediating Role of Self-Control

Abstract: Background Excessive social media consumption leads to addiction and affects mental health. It is a phenomenon that is difficult to avoid. Previous research on the effects of excessive Internet use shows that people who engage in social media (SM) without restraint experience over-involvement, over-disclosure, technostress, and social media fatigue (SMF). SMF, conceptualized as an emotional and cognitive feeling of being overwhelmed, manifests itself in mindless browsing of content, limiting the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 95 publications
1
1
0
1
Order By: Relevance
“…The study findings have also shown a significant association between SA and fatigability, as observed in previous studies; increased boredom, fatigue, exhaustion, and frustration have been reportedly linked to SA [73,74].…”
Section: Discussionsupporting
confidence: 85%
“…The study findings have also shown a significant association between SA and fatigability, as observed in previous studies; increased boredom, fatigue, exhaustion, and frustration have been reportedly linked to SA [73,74].…”
Section: Discussionsupporting
confidence: 85%
“…There is some discussion in practice on how consumption of social media content may, at times, be viewed as mindless, given the automaticity and continuous supply of content in the form of pictures and videos (e.g. Świątek et al , 2023). We find that more mindful individuals tend to interpret gaps between their ideal and actual self as opportunities for growth and reasons to feel inspired, motivated and determined to achieve that ideal, mindful of what is likely to be plausible and what is likely to be fake or staged and thus, not viable as an ideal self.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…10 ( 19), 165 -181. https://doi.org/10.55560/arete.2024.19.10.9 Mašková, 2023). La justificación epistemológica radicó en la comprobación teóricacientífica de los instrumentos utilizados de forma cuantitativa y cualitativa para conocer la incidencia del tecnoestrés en el DA en estudiantes que cursan una malla curricular y ocupacional con altas exigencias y demanda laboral (Köslich-Strumann et al, 2023;Aguayo-Estremera et al, 2023;Fortea et al, 2023;Świątek et al, 2023).…”
Section: Introductionunclassified